2022
DOI: 10.3389/fmicb.2021.787451
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Antimicrobial Resistance of Clostridioides difficile in Hospitalized Patients From Mexico

Abstract: Clostridioides difficile is a global public health problem, which is a primary cause of antibiotic-associated diarrhea in humans. The emergence of hypervirulent and antibiotic-resistant strains is associated with the increased incidence and severity of the disease. There are limited studies on genomic characterization of C. difficile in Latin America. We aimed to learn about the molecular epidemiology and antimicrobial resistance in C. difficile strains from adults and children in hospitals of México. We studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 80 publications
0
21
1
1
Order By: Relevance
“…However, the epidemic keeps evolving, and new clades have emerged with a wide diversity of genotypes in different countries (Clades 1, 2, 3, 4, and 5 and one cryptic clade have been described) (23,24). Studies in large numbers of strains have shown that clade 1 is more prevalent worldwide, whereas, in Mexico, we found clade 2/ST1 strains to the more prevalent, in isolates from both adults and children (6) C. difficile isolates of the molecular type Clade2/ST1 have been associated with severe disease and in hospital outbreaks, and it has been suggested that these "hypervirulent" strains produce higher levels of TcdA and TcdB toxins besides the CDT toxin (28).In the present work, we found clade 2/ST1 as the most prevalent and extensively studied cytotoxicity, toxins profile, toxins expression, and whole-genome phylogeny.As suggested, most of these clade 2/ST1 strains presented the toxins profile tcdA+ tcdB+cdtA+ cdtB+.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, the epidemic keeps evolving, and new clades have emerged with a wide diversity of genotypes in different countries (Clades 1, 2, 3, 4, and 5 and one cryptic clade have been described) (23,24). Studies in large numbers of strains have shown that clade 1 is more prevalent worldwide, whereas, in Mexico, we found clade 2/ST1 strains to the more prevalent, in isolates from both adults and children (6) C. difficile isolates of the molecular type Clade2/ST1 have been associated with severe disease and in hospital outbreaks, and it has been suggested that these "hypervirulent" strains produce higher levels of TcdA and TcdB toxins besides the CDT toxin (28).In the present work, we found clade 2/ST1 as the most prevalent and extensively studied cytotoxicity, toxins profile, toxins expression, and whole-genome phylogeny.As suggested, most of these clade 2/ST1 strains presented the toxins profile tcdA+ tcdB+cdtA+ cdtB+.…”
Section: Discussionmentioning
confidence: 53%
“…Shortly after the identification of hypervirulent C. difficile strains RT 027 (B1/NAP1/ST1) in Canada, there were reports of CDI outbreaks caused by this strain in the United States and Europe and then Asia, Australia, and Latin America (3). In Mexico C. difficile RT-027 strain has been confirmed in hospitalized patients (4,5,6). The clinical outcome of C. difficile infection (CDI) ranges from mild diarrhea to lifethreatening pseudomembranous colitis, where virulence is mainly driven by the action of toxin A (TcdA) and toxin B (TcdB).…”
Section: Introductionmentioning
confidence: 99%
“…Each sample was used to produce a sequencing library with gDNA that was of sufficient quality (A 260/280 and A 260/230 > 1.5) with an average insert size of 350 bp according to the KAPA HyperPlus Kit protocol as described previously [ 16 , 17 , 18 , 19 ]. All samples were sequenced using HiSeq XTEN Sequencing System (Illumina, San Diego, CA, USA) [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Susceptibility of H. pylori ZJC03 to amoxicillin, metronidazole, tetracycline, and clarithromycin was evaluated by the epsilometric method (E-test) ( 20 ). The E-test strip containing antibiotics was attached to the surface of the agar medium containing H. pylori (10 8 CFU/mL) and cultured in a microaerophilic tank (85 N 2 , 10 CO 2 , and 5% O 2 ) at 37°C for 48 h−72 h. The minimal inhibitory concentration (MIC) was determined by the point of the antibacterial ring and the strip.…”
Section: Methodsmentioning
confidence: 99%